A Test Method for Creep Characteristics of Loess Based on the One-Dimensional Consolidator - Rongbin Huang; Shuangming Wang; Shuancheng Gu; Zhengjun Mao (Advances in Civil Engineering)
When the traditional one-dimensional consolidator is used to study the creep characteristics of loess, due to the hoop effect of the ring cutter, only the attenuation creep stage and stable creep stage of loess can be studied, but the accelerated creep stage cannot be presented. In order to avoid the influence of drilling on the creep characteristics of loess, the paper improves the consolidation instrument by drilling holes along the diameter direction in the center of the sample to provide artificial space for soil failure. At the same time, the sample size is increased to ensure that the diameter of the sample is greater than five times of the diameter of the borehole, so as to avoid the influence of drilling on the creep characteristics of loess. The creep characteristics of loess are studied by step loading (vertical pressure at all levels is 125 kPa, 175 Pa, 225 kPa, and 275 kPa), and the whole creep process characteristic curves of loess under different stress conditions are obtained. An endoscope was placed in the hole to observe the deformation and failure characteristics of loess in different stages of creep. This method makes up for the defect that the traditional one-dimensional consolidator cannot obtain the whole process characteristics of loess creep. At the same time, it has the advantages of simple operation, less external influence factors, stronger data reliability, and can directly observe the changes of loess creep soil. It has a beneficial role in promoting the experimental research of loess creep characteristics.